If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -5n = 5m + 7 Reorder the terms: 8m + -5n = 7 + 5m Solving 8m + -5n = 7 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 8m + -5m + -5n = 7 + 5m + -5m Combine like terms: 8m + -5m = 3m 3m + -5n = 7 + 5m + -5m Combine like terms: 5m + -5m = 0 3m + -5n = 7 + 0 3m + -5n = 7 Add '5n' to each side of the equation. 3m + -5n + 5n = 7 + 5n Combine like terms: -5n + 5n = 0 3m + 0 = 7 + 5n 3m = 7 + 5n Divide each side by '3'. m = 2.333333333 + 1.666666667n Simplifying m = 2.333333333 + 1.666666667n
| 6x+20=4x+13 | | log(y)=9t-4 | | 76=x^3+3*x | | 8x+2=7(x-2)+4 | | 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p | | y=kx+5 | | F(x)=15x-8 | | 5(5x-4)+11=-3 | | 7-3m=40 | | c+14c+11=7c-13 | | -2(0)+1=5-2(0) | | 2m-8=19-m | | 2(3d+c)-(4d+2c)= | | -2f=2+1-2f | | 7-3(m)=40 | | -3w+3=3-3w |